Undergraduate students acceptance of library online database system to support studies and research - Azlan, Nur Athirah; Zaulkifli, Zahidah; Hussin, Husnayati; Samsuri, Suhaili; Md Ali, Asma (IEEE, 2016)
This paper reports on the user acceptance test (UAT) result that examine participants’ acceptance of a library online database system that has been developed to support the process of studies and research among under graduate students. The objectives of the user acceptance test are to ensure the new system does what it set out to do and meets the requirements the business has of it. In order to test the system that is expected to cooperate with user demands and expectations, certain variables have been taken into consideration. The variables were taken from the requirements collected from a survey that has been collected earlier. The variables were then categorized into four categories mainly People, System Usability, System Features and User Satisfaction. A single case study has been employed in this evaluation which included undergraduate students from International Islamic University Malaysia (IIUM) as participants. These participants are directly involved in the usage of an online database system in IIUM. The user evaluation is carried out in two phases. The first phase involves a task-based approach where participants are given several tasks to perform while using the system. The second phase is a questionnaire to elicit the participants' feedback on the perceived usefulness of the system after they have completed the tasks given. The user acceptance test of the Library Online Database System (LODS) in serving the undergraduate students has been reflected by the positive feedback from the 15 participants. The findings signify a positive reaction from participants towards the system. The system, in general, has been perceived as useful to support studies and research works among undergraduate students electronically.